2005
DOI: 10.1038/sj.npp.1300858
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Pain Induces Anxiety with Concomitant Changes in Opioidergic Function in the Amygdala

Abstract: Clinically, it has been reported that chronic pain induces depression, anxiety, and reduced quality of life. The endogenous opioid system has been implicated in nociception, anxiety, and stress. The present study was undertaken to investigate whether chronic pain could induce anxiogenic effects and changes in the opioidergic function in the amygdala in mice. We found that either injection of complete 35 S]GTPgS binding in membranes of the amygdala was significantly suppressed by CFA injection or nerve ligation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
202
7
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 250 publications
(232 citation statements)
references
References 35 publications
(35 reference statements)
18
202
7
5
Order By: Relevance
“…Although the neurobiological mechanisms underlying the effects of MD on nociceptive responding in adulthood remain unknown, it has been shown that MD induces a range of sex-dependent developmental and psychoneuroimmunendocrine alterations 54 . It has been proposed that Alterations in affective responding such as anxiety-and depressive-like behaviours have been shown to be induced in a number of models of peripheral nerve injury 45,47,51,57 , although in the present study SNL failed to modulate affective behaviour. The short period following surgery over which these behaviours were examined (Day16), may account for the lack of effects as previous studies have indicated that alterations in affective behaviour only manifest after at least a month post-surgery 45,51,57 .…”
Section: Discussioncontrasting
confidence: 53%
“…Although the neurobiological mechanisms underlying the effects of MD on nociceptive responding in adulthood remain unknown, it has been shown that MD induces a range of sex-dependent developmental and psychoneuroimmunendocrine alterations 54 . It has been proposed that Alterations in affective responding such as anxiety-and depressive-like behaviours have been shown to be induced in a number of models of peripheral nerve injury 45,47,51,57 , although in the present study SNL failed to modulate affective behaviour. The short period following surgery over which these behaviours were examined (Day16), may account for the lack of effects as previous studies have indicated that alterations in affective behaviour only manifest after at least a month post-surgery 45,51,57 .…”
Section: Discussioncontrasting
confidence: 53%
“…A tendency to remain in the peripheral zone of an open fi eld has been described in various animal models. 25,26) Reduced activity and exploration in OFT refl ects a deterioration of the natural behavioral tendencies of the rats and may be a result of postsurgical pain. 27) A similar pattern of behavior was observed in EPM.…”
Section: Discussionmentioning
confidence: 99%
“…When pain becomes chronic, the sensory dysfunction is accompanied by several brain disorders, such as anxiety, amnesia and depression (Ling et al, 2007;Narita et al, 2006). Cumulative behavioral, electrophysiological and molecular data suggested important roles for the hippocampal formation (HF) in pain process (Cecarelli et al, 1999;Liu & Chen, 2009).…”
Section: Introductionmentioning
confidence: 99%